2009
DOI: 10.1177/1076029609339747
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Aggregation in Children With Helicobacter pylori Infection

Abstract: This study was performed to investigate the platelet aggregation alterations in platelet-rich plasma (PRP) samples of children with Helicobacter pylori (H pylori) infection. Platelet aggregation induced by adenosine diphosphate (ADP), collagen, ristocetin, or epinephrine was studied with photometric aggregometry in 30 patients before and after eradication therapy and in a control group including 15 children. The pretreatment mean maximum aggregation values and slope were significantly lower (P < .0001) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A study conducted by Gursel et al. showed that H. pylori infection may cause dysfunction of platelets in children and can be reversed by H. pylori eradication [16]. Those studies clearly demonstrate the existence of a close interaction between H. pylori and platelets, which surely merits further investigation.…”
Section: Hematologic Diseasesmentioning
confidence: 95%
“…A study conducted by Gursel et al. showed that H. pylori infection may cause dysfunction of platelets in children and can be reversed by H. pylori eradication [16]. Those studies clearly demonstrate the existence of a close interaction between H. pylori and platelets, which surely merits further investigation.…”
Section: Hematologic Diseasesmentioning
confidence: 95%
“…A multi-center randomized controlled trial of H. pylori eradication in children with chronic ITP failed to show an effect of H. pylori eradication on platelet recovery [40]. Ferrara et al reported a positive effect of H. pylori eradication on the outcome of children with chronic ITP with a positive stool antigen test, although their study was not a randomized controlled trial [41].…”
Section: Idiopathic Thrombocytopenic Purpura (Itp) and Platelet Dysfumentioning
confidence: 99%
“…A multi‐center randomized controlled trial of H. pylori eradication in children with chronic ITP failed to show an effect of H. pylori eradication on platelet recovery [40]. Ferrara et al.…”
Section: Extra‐intestinal Manifestationsmentioning
confidence: 99%
“…All these studies have raised a question whether H. pylori infection affects platelet functions. On the other hand, Gursel et al [3] demonstrated that H. pylori infection in children may significantly decrease platelet response to ADP (ADP-like defect), which can be reversed by eradication therapy.…”
Section: Discussionmentioning
confidence: 99%